2010
DOI: 10.1057/jdg.2010.17
|View full text |Cite
|
Sign up to set email alerts
|

Disclosure of non-audit services in annual reports and auditor independence: Evidence from Italy

Abstract: This article explores recent regulatory reforms in Italy and analyzes the fi rst-time application of mandatory disclosure in annual reports of audit and non-audit fees. This information can convey to readers of fi nancial statements an indication of auditor independence (in appearance). An empirical analysis is conducted on annual reports of 239 Italian listed companies for the year 2007.The main research objectives are as follows: (1) to provide a comprehensive description of the relative level of non-audit f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Non-audit fees received by the auditors indicate that there is a greater economic dependence on their clients. Ahmad et al (2006) and Ianniello (2010) highlight that economic dependency on a client's fees can impair the auditor's independence. Similarly, Abdul Wahab et al (2020) found that provisions of non-audit services create economic bonding and can pose a threat to auditor independence among Malaysian firms.…”
Section: Auditor Independence and Earnings Managementmentioning
confidence: 99%
“…Non-audit fees received by the auditors indicate that there is a greater economic dependence on their clients. Ahmad et al (2006) and Ianniello (2010) highlight that economic dependency on a client's fees can impair the auditor's independence. Similarly, Abdul Wahab et al (2020) found that provisions of non-audit services create economic bonding and can pose a threat to auditor independence among Malaysian firms.…”
Section: Auditor Independence and Earnings Managementmentioning
confidence: 99%
“…There are researchers who consider specifically tax services (e.g., Aschauer andQuick, 2018, Kwak andPark, 2020). Another group of researchers distinguishes three basic NAS categories: audit-related, tax, and other services (e.g., Ianniello, 2011;Wahab, Gist and Majid, 2014). On the other hand, Ezzamel, Gwilliam, and Holland (2002) explore five NAS types: accounting-related, finance advice, tax services, management consultancy, and other non-audit services.…”
Section: Definition Of Nas and The Importance Of Their Disclosurementioning
confidence: 99%
“…58/1998, known as TUF – Testo Unico sulla Finanza , Unified Financial Act), the issue was not resolved. Overall, the Consob communications indicate that, despite the legal limitation of activity in the auditing firms' bylaws, there were elements of ambiguity in the implementation of that rule (Ianniello, 2011).…”
Section: Italian Regulatory Environment: From Opacity To Disclosurementioning
confidence: 99%
“…For the second objective, the research hypothesis is tested by applying the parametric t ‐test and the nonparametric Two‐sample Wilcoxon rank‐sum (Mann–Whitney) test to the average NAF percentages of the non‐qualified and qualified groups of companies. Based on the results of Ianniello (2011), we also focus our attention on the group of unqualified companies with an emphasis of matter paragraph in their audit report. This aspect was not explicitly measured in other studies on the subject under investigation.…”
Section: Research Design and Findingsmentioning
confidence: 99%
See 1 more Smart Citation